2021
DOI: 10.3389/fnagi.2021.657308
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Brain Activity With Age During a Game-Like Dynamic Balance Task: Single- vs. Dual-Task Performance

Abstract: Background: Postural control and cognition are affected by aging. We investigated whether cognitive distraction influenced neural activity differently in young and older adults during a game-like mediolateral weight-shifting task with a personalized task load.Methods: Seventeen healthy young and 17 older adults performed a balance game, involving hitting virtual wasps, serial subtractions and a combination of both (dual-task). A motion analysis system estimated each subject's center of mass position. Cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
9
1
Order By: Relevance
“…This would nicely explain why younger adults demonstrated higher activity in PoCG than older adults in the present study. In contrast to our findings, another fNIRS study by de Rond et al (2021) has recently reported higher PoCG activation in the older compared to the younger in a game-like weight-shifting task, irrespective of task load. These differing results might, for example, be caused by the different nature of the task investigated (thus requiring different postural control strategies) or different equipment used.…”
Section: Discussioncontrasting
confidence: 99%
“…This would nicely explain why younger adults demonstrated higher activity in PoCG than older adults in the present study. In contrast to our findings, another fNIRS study by de Rond et al (2021) has recently reported higher PoCG activation in the older compared to the younger in a game-like weight-shifting task, irrespective of task load. These differing results might, for example, be caused by the different nature of the task investigated (thus requiring different postural control strategies) or different equipment used.…”
Section: Discussioncontrasting
confidence: 99%
“…As another reason, the maintenance or repetition of some actions or tasks has attracted the greater observation of the change or activation of specific cerebral cortices, especially for the dual task, which is a popular method for investigating the increased risk of falls in the elderly. Studies have reported a similar conclusion that the activation of PFC in older people is enhanced more than that in young people when performing balance tasks [ 41 , 42 , 43 ]. This phenomenon is often explained by the theory of “compensation”, which is defined as the neural recruitment that enhances task performance in healthy aging [ 44 ].…”
Section: Discussionmentioning
confidence: 75%
“…Finally, the increase in steering variability and decrease in task performance could also stem from the decrease in dual-tasking abilities with aging [19,38,39]. The shoulder check task requires participants to simultaneously bike straight and look behind.…”
Section: Discussionmentioning
confidence: 99%